(untitled) (Biodiversitas Journal of Biological Diversity, 2018)
Asmara IY, Garnida D, Tanwiriah W, Partasasmita R. 2019. Qualitative morphological diversity of female Pelung Chickens in West Java, Indonesia. Biodiversitas 20: 126-133. Pelung chickens are indigenous chickens in Indonesia derived from Cianjur District, West Java Province. The chickens which are raised as singing chickens have a distinctive body shape compared to other local chickens. Regular contests are conducted as a media to show singing ability and performance including morphological characteristics of Pelung chickens. Pelung keepers believe that the chickens inherited their singing capability from their parents. Pelung keepers perceived qualitative traits for example plumage color as an indicator of a good female breed. The objective of this study was to determine the qualitative traits of female Pelung Chickens in West Java. This study recorded comb type, color of eye, beak, skin, plumage and shank including traditional name related to the morphological traits. A survey was conducted to gather data involving 160 chickens in four districts in West Java Province, including Cianjur, Sukabumi, Bandung, and Garut Districts. The results showed that adult female Pelung chickens have similar qualitative characteristics except for plumage color. The majority of pelung chickens in Bandung, Garut, and Sukabumi have black plumage, while in Cianjur District have yellow-brown color. The chicken contest seems to be the main factor dictating keepers’ preferences in terms of plumage color in Bandung, Garut and Sukabumi Districts. This study indicates a decreasing variation in plumage color of female Pelung chickens. These findings are important in terms of breeding strategy of Pelung chickens.